2014
DOI: 10.1002/wrna.1266
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs with big implications: new insights into H/ACA snoRNA function and their role in human disease

Abstract: A myriad of structurally and functionally diverse non-coding RNAs (ncRNAs) have recently been implicated in numerous human diseases including cancer. Small nucleolar RNAs (snoRNAs), the most abundant group of intron-encoded ncRNAs, are classified into two families (box C/D snoRNAs and box H/ACA snoRNAs) and are required for post-transcriptional modifications of ribosomal RNA (rRNA). There is now a growing appreciation that nucleotide modifications on rRNA may impart regulatory potential to the ribosome, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 115 publications
4
123
1
1
Order By: Relevance
“…Ψ formation is catalyzed by diverse pseudouridine synthases (PUSs), which break the carbon-nitrogen bond of uridine and create a carbon-carbon bond by attaching the C5 position of the cleaved uridine to the ribose (Charette and Gray 2000). PUSs can either act in a site-specific manner, by directly recognizing their substrates, or can be guided to their targets via H/ACA box snoRNAs (Charette and Gray 2000;Spenkuch et al 2014;McMahon et al 2015).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Ψ formation is catalyzed by diverse pseudouridine synthases (PUSs), which break the carbon-nitrogen bond of uridine and create a carbon-carbon bond by attaching the C5 position of the cleaved uridine to the ribose (Charette and Gray 2000). PUSs can either act in a site-specific manner, by directly recognizing their substrates, or can be guided to their targets via H/ACA box snoRNAs (Charette and Gray 2000;Spenkuch et al 2014;McMahon et al 2015).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…46 We have recently begun to analyze the C at the wholetranscriptome genome level using a methodology similar to that used in recent studies that performed whole transcriptome mapping of this modification. 47 It will be of great interest to compare the pattern during the 2 life stages of the parasite and examine if these changes are correlated with growth at different temperatures, and/or are essential for preferential translation of distinct mRNAs which are developmentally regulated.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the translation of distinct mRNA species requires different types of modification and that a particular pattern is favored to translate mRNAs that are essential for the survival and metastasis of cancer cells. 46 Thus, novel snoRNAs with different function may arise in all organisms from Leishmania to man by just changing the pocket. Indeed, in Euglena as well, recent studies suggest that frequent gene duplication is a common mechanism driving snoRNA emergence leading to both a large number of snoRNAs and clustered patterning of rRNA modification.…”
Section: Discussionmentioning
confidence: 99%
“…The pseudouridylation of rRNAs, targeted by the H/ACA RNP complex, occurs in regions critical for ribosome activity such as the decoding center or peptidyl transferase domain. Pseudouridylation affects translation fidelity, stop codon usage and is required for IRES-mediated translation [76,78,79] . Alterations in the H/ACA snoRNP complex is most prominent in leukemias but is also altered in some solid tumors, including: prostate, head and neck, and non-small cell lung cancer [79] .…”
Section: Shwachman-bodian-diamond Syndrome Protein (Sbds)mentioning
confidence: 99%